Konstruksi Media Terhadap Berita Awal Munculnya Covid-19 di Indonesia (Analisis Framing Pada Berita Detik.com dan Kompas.com) - Urip Mulyadi; Mubarok Mubarok (Avant Garde, 2021)
Covid-19 announcement of the case the first time in Indonesia directly by the President Jokowi has made people panic. Because most of the information circulating on social media comes from online media. The role of the media in a pandemic is as important as doctors and medical personnel, because usually health issues in Indonesia are rarely a concern. This study aims to determine how Detik.com and Kompas.com framing about the COVID-19 outbreak in Indonesia. The method used in this research is the analysis of media text context with data analysis through the Pan and Kosicky framing model using the constructivism paradigm through qualitative research methods. The results showed that Detik.com and Kompas.com perform media functions as a social control with the same framing in response to a situation of panic in the community after President Jokowi announced two positive first citizen Covid-19 in Indonesia. In general, the framing of the news carried out by the two online media has the same theme in informing efforts to deal with the pandemic calmly, moving a healthy lifestyle, not panic buying and anticipating the worst.